A PRELIMINARY STUDY ON BENTHIC AND ARBOREAL FAUNA ASSOCIATED WITH MANGROVE Rhizophora Mucronata ON THE EAST COAST OF MAURITIUS (INDIAN OCEAN) WITH SPECIAL REFERENCE TO THE MOLLUSCA - Chandani Appadoo; Nabiihah B. Roomaldawo (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Mangrove ecosystems are important as they harbour a diversity of life forms. This study aimed at studying the benthic and arboreal macrofaunal diversity and abundance associated with three naturally occurring mangrove forests of Mauritius, Western Indian Ocean. The mangrove areas included Roches Noires, Mahebourg and Pointe Maurice, on the east coast of the island. The field study was carried out at low tide during summer season from October 2003 to February 2004. At each of the three sites, the arboreal and benthic macrofauna were sampled separately, using quadrats of 1 m x 1 m and 25 cm x 25 cm, respectively. Sixty-four benthic and 42 arboreal quadrats were collected from Roche Noires, 40 benthic and 41 arboreal quadrats at Mahebourg and 40 benthic and 30 arboreal quadrats at Pointe Maurice. The results showed that benthic habitat is more diverse with regards to molluscan families (24 families) than the arboreal habitat (5 families). Pointe Maurice has a more diverse benthic fauna. Relative percentage abundance and mean density of molluscan families are reported. Highest mean densities and relative abundance were recorded for the Family Littorinidae among arboreal macrofauna. In benthic macrofauna, the highest mean densities and relative abundance were noted in Family Cerithiidae at Roches Noires and Mahebourg.